Six espèces nouvelles de Dactylogyridae (Platyhelminthes, Monogenea) parasites des branchies de cichlidés (Teleostei, Cichliformes) du bassin du Bas Congo - Jorissen, Michiel W P; Pariselle, Antoine; Huyse, Tine; Vreven, Emmanuel J; Snoeks, Jos; Decru, Eva; Kusters, Thomas; Lunkayilakio, Soleil Wamuini; Bukinga, Fidel Muterezi; Artois, Tom; Vanhove, Maarten P M (Parasite, 2018)
The Lower Congo Basin is characterized by a mangrove-lined estuary at its mouth and, further upstream, by many hydrogeographical barriers such as rapids and narrow gorges. Five localities in the mangroves and four from (upstream) left bank tributaries or pools were sampled. On the gills of Coptodon tholloni, Coptodon rendalli, Hemichromis elongatus, Hemichromis stellifer and Tylochromis praecox, 17 species of parasites (Dactylogyridae & Gyrodactylidae, Monogenea) were found, eight of which are new to science. Six of these are herein described: Cichlidogyrus bixlerzavalai n. sp. and Cichlidogyrus omari n. sp. from T. praecox, Cichlidogyrus calycinus n. sp. and Cichlidogyrus polyenso n. sp. from H. elongatus, Cichlidogyrus kmentovae n. sp. from H. stellifer and Onchobdella ximenae n. sp. from both species of Hemichromis. On Cichlidogyrus reversati a ridge on the accessory piece was discovered that connects to the basal bulb of the penis. We report a putative spillback effect of the native parasites Cichlidogyrus berradae, Cichlidogyrus cubitus and Cichlidogyrus flexicolpos from C. tholloni to the introduced C. rendalli. From our results, we note that the parasite fauna of Lower Congo has a higher affinity with the fauna of West African and nearby freshwater ecoregions than it has with fauna of other regions of the Congo Basin and Central Africa.
Keywords: Animals; ploštěnci; biodiverzita; Gills; Phylogeography; cichlidy; infekce červy třídy Trematoda; Trematode Infections; nemoci ryb; Fish Diseases; žábry; Fresh Water; Phylogeny; Congo; Cichlids; sladká voda; fylogeografie; Biodiversity; Platyhelminths; zvířata; Kongo; fylogeneze